Strategi Redaksi Catch Me Up! Dalam Menghadapi Persaingan Industri Media Online - Aaron Reghanada Prasetyawibowo; Ni Made Ras Amanda Gelgel; I Gusti Agung Alit Suryawati (Universitas Gadjah Mada, 2021)
Catch Me Up! is a pioneering online media that has innovation through daily newsletters. In addition, the language features brought by Catch Me Up! using everyday Indonesian which is used by many millennial generations. This study aims to determine how the implementation of the Catch Me Up! in the face of competition in the online media industry. This research is reviewed based on the application of media management and editorial strategies used using 4 management functions of George R Terry with implementation of actuating process from Tommy Suprapto. To describe it, this research uses qualitative research methods. Primary data was obtained based on the results of in-depth interviews with 2 key-informants, while secondary data was obtained from the study of literature. The results of this study show the editorial strategy of Catch Me Up! included in the implementation stage. Analysis of the functions of planning, organizing, actuating and controlling shows Catch Me Up! has an editorial strategy in facing the online media industry competition, namely by making a daily newsletter using everyday language that is easily understood by the public. Everything is done through editorial management so that the quality of the content produced is in accordance with the standards.